From E-Government to Smart Governance: Institutional Adoption of the Jogja Smart Service Application in Yogyakarta City - Kristina Setyowati; Salsabila Inas Sausan; Septyanto Galan Prakoso; Berlian Berlian (Profetik: Jurnal Komunikasi, 2026)
Jogja Smart Service (JSS) is a digital public service application developed by Dinas Komunikasi, Informatika dan Persandian Kota Yogyakarta to support independent services. E-Government Adoption is necessary because its concept has become a reference in realizing electronic-based governance, especially in simplifying services through the development of digital applications. This study uses descriptive qualitative research methods; data were collected through semi-structured interviews, non-participant observation, and documentary analysis with eleven informants selected through purposive sampling, and validity was established using methodological triangulation. This research was studied using Indrajit’s theory (2005), which contains components of E-Government adoption, including Competency Building, Capital, Cyber Laws, Connectivity, Content Development, and Citizen Interfaces. The results of the study shows that each of the adoption components has been largely met, with some components only partially fulfilled. The findings indicate that the adoption of E-Government principles in the Jogja Smart Service (USS) application has generally been implemented, although several components still require improvement. Competency Building is reflected through employee training programs that are not yet conducted routinely. The Capital component shows that JSS development is primarily funded through the Regional Revenue and Expenditure Budget (APBD), with additional ecosystem support from CSR initiatives. Cyber Laws are supported by central and regional regulations. Connectivity is supported by hardware and software infrastructure at DISKOMINFO Yogyakarta City, although system scalability and performance still require continuous evaluation. Content Development is reflected in the application's accessible interface and integrated services, while improvements in responsiveness and user experience remain necessary. Citizen Interfaces are demonstrated through multi-access communication channels for public services.